PIV investigation of acoustic transmission through curved duct bends for the optimisation of thermoacoustic systems - Wee, David Shuon Tzern (2015)
The efficiency of travelling wave thermoacoustic system, for a given operating temperature difference, is determined by the acoustic wave transmission through its feedback resonator loop system. Curved duct bends are one of the most repeated components used in the construct of these feedback resonator systems and thus require acoustic transmission optimisation. This research investigates the transmission of low frequency, high amplitude acoustic waves propagating through duct bends with different radius of curvatures using Particle Image Velocimetry (PIV). The experimental PIV investigation was conducted on the axial plane of the bend. The velocity vector maps obtained from each run was analysed using both the newly developed Velocity based Wave Decomposition (VWD) technique as well as the Proper Orthogonal Decomposition (POD) technique. The POD technique was shown to successfully separate the different flow component of the acoustic wave in the respective Proper Orthogonal Modes (POMs). The acoustic transmission was thus computed based on the strength of these POMs. The POMs also allowed for the flow visualisation of the different loss mechanism that exists within the wave propagating through the bend (most notably, the energy cascade loss mechanism). Based on the quantitative measurement of the acoustic transmission as well as the qualitative flow observation of the different loss mechanism, a non-dimensional parameter was developed in order to characterise the acoustic transmission through curved duct bend systems. This parameter is known as the Strouhal-Dean number. Based on this parameter, the acoustic transmission can be characterised into 3 acoustic flow regimes: Viscous dominated oscillation, Inertia dominated oscillation and the Transition regime between the first two oscillation regimes. The optimum acoustic transmission range corresponded to the transition regime where the inertia generated secondary circulation was balanced by its viscous loss suppression. The optimal Strouhal Dean number for acoustic transmission was found to be approximately 10.8.